2008
DOI: 10.1038/ncpneph0655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Disease: erythropoietin resistance in patients with both heart and kidney failure

Abstract: Anemia is common in patients who have both heart failure and chronic kidney disease, and there is an association between anemia and progression of both diseases. The main causes of anemia are deficient production of erythropoietin (EPO), iron deficiency, and chronic disease with endogenous EPO resistance. EPO has been successfully used for over a decade to treat anemia in patients with chronic kidney disease. Less obvious are the safety and efficacy of EPO treatment in patients with both heart failure and rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
110
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 100 publications
1
110
0
1
Order By: Relevance
“…Patients with PIH had not only a higher EPO use but also, lower hemoglobin levels, indicating some degree of EPO resistance. An obvious link may exist between the EPO hyporesponsiveness and the aforementioned inflammatory phenotype of patients with PIH, which may result in limited iron availability, a reduced number of EPO receptors, and impaired EPO receptor signaling (46). Recent evidence suggests that hypoxemia may affect erythrocyte resilience against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PIH had not only a higher EPO use but also, lower hemoglobin levels, indicating some degree of EPO resistance. An obvious link may exist between the EPO hyporesponsiveness and the aforementioned inflammatory phenotype of patients with PIH, which may result in limited iron availability, a reduced number of EPO receptors, and impaired EPO receptor signaling (46). Recent evidence suggests that hypoxemia may affect erythrocyte resilience against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The scenario of EPO levels that are inappropriately low for the degree of anemia (although in absolute values may be even higher than in the healthy population) (25) has been described in a variety of chronic diseases including congestive heart failure and CKD (17,26). Several inflammatory mechanisms may contribute to this phenomenon of EPO resistance, such as inhibition of the growth of erythroid progenitor cells, down-regulation of EPO-receptor expression, mediation of antagonistic binding to the EPO receptor, and inhibition of downstream signaling cascades (26). Our results that elevated EPO levels were in large part related to the level of inflammation are in line with the described mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in anemia of chronic disease and anemia of cancer, data suggest that hepcidin concentrations are increased, causing decreased absorption of iron and increased sequestration of iron in the reticuloendothelial system, which together account for the observed anemia [1,2,14,19,22]. It is also suggested that patients with chronic kidney disease may have increased hepcidin, which could contribute to their observed renal anemia that is treated with erythropoietin and oral iron [4,24].…”
Section: Introductionmentioning
confidence: 81%